Solvent Extraction of Pd(CN)42– from Alkaline Cyanide Solution with Dodecyl Trimethylammonium Bromide - Chen, Lei; Huang, Zhangjie; Chen, Jing; Liu, Minhong (Asian Journal of Chemistry, 2014)
The solvent extraction of Pd(CN)42- from alkaline cyanide solution by using dodecyltrimethylammonium bromide diluted in benzene was investigated. It has been indicated that Pd(CN)42- extraction percentage increases by increasing dodecyltrimethylammonium bromide concentration. Extraction parameters of Pd(CN)42-, including appropriate diluting agent, dodecyltrimethylammonium bromide concentration, contact time of aqueous and organic phases, pH of the aqueous solution and organic/aqueous phase ratio, were studied. Octanol has an obvious synergistic effect on Pd(CN)42- extraction with dodecyltrimethylammonium bromide. It was indicated that at dodecyltrimethyl ammonium bromide concentration 0.01 mol L-1, contact time of 10 min, octanol concentration 40 % (v/v), organic/aqueous phase ratio 1, the optimal pH of the aqueous phase11.5, almost all of the Pd(CN)42-(> 99 %) was transferred from the aqueous phase into the organic phase. Ammonium thiocyanate solution could be used as stripping agent. Most of the Pd(CN)42- in the organic phase can be stripped with aqueous solutions of ammonium thiocyanate.